Exploring Risks and Rewards Associated with High Performance Manufactured Buildings - Hargroves, Charlie; Hebert, Lio; Newman, Peter; Green, Jemma; Conley, Daniel (2017)
The transition to the offsite construction and manufacture of buildings stands to create a lucrative opportunity for the global building sector. The shift to the manufacture of buildings stands to generate numerous benefits including economic benefits (such as construction times for major commercial construction projects substantially, social benefits (significantly improving workplace occupational health and safety by bringing the majority of building construction indoors), and environmental benefits (through reduced materials wastage, reduced materials transportation, greater inclusion of energy and water efficient elements, and the potential for greater use of recycled materials). This paper explores a range of factors that affect the attractiveness of such benefits along with the perception of the associated risks related to the fact that for instance in order to provide the access to capital needed to significantly upscale building manufacture long standing financing structures need to be redesigned in the building sector related to providing progress payments and dealing with completion risk. The paper is informed by an industry workshop held by Sustainable Built Environment National Research Centre (SBEnrc) in Australia, in collaboration with the EU Centre for Global Affairs at the University of Adelaide and prefabAUS, on the topic of “Capturing Opportunities from Financing Offset Building Manufacture”. The workshop was held as an official partner event as part of the European Union’s Green Week 2016. The workshop was well attended with 25 representatives from banks, builders, government agencies and researchers. In-line with the Green Week theme of “Investing in the Future” the workshop focused on how the banking community perceived risks and rewards from investing in the manufacture of buildings in Australia.